Non-traditional cement and concrete 6th International Conference Non-Traditional Cement and Concrete 2017 - Nenadálová, Šárka; Bílek, Vlastimil; Keršner, Zbyněk; Seitl, Stanislav; Šimonová, Hana (Key engineering materials, 2018)
Annotation This book based on results of the 6th International Conference Non-Traditional Cement and Concrete 2017 (Brno, Czech Republic from June 19 to June 22, 2017) and includes recent results of the scientific research in the area of non traditional cements and concretes, especially alkali activated materials, geopolymers, clinker-free binders, durability, high performance concrete, microstructure study etc. We hope that this collection will be useful for many specialists whose activities are related to building materials.